Firmiana daweishanensis sp. nov. (Malvaceae) from Southeast Yunnan, China - Zhang, Guiliang; Cai, Lei; Duan, Jieqiu; Wang, Ting; Xiang, Jianying (Phytotaxa, 2020)
A new species of Malvaceae, Firmiana daweishanensis Gui L.Zhang & J.Y.Xiang from Southwest Yunnan, China, is described and illustrated here. It is similar to F. hainanensis in its bark and leaf shape, while its flower is quite similar to F. major. However, it is obviously different from both species by its character of proteranthus (flowering before the leaves), which is the critical character of Erythropsis distinguishing from Firmiana with hysteranthus (flowering after the leaves) character. Moreover, the androecium of F. daweishanensis is consisting of more than 30 sessile 2-celled anthers while that of the other two species only 10–15 anthers. The discovery of this species supports the idea that Firmiana and Erythropsis may be indistinct. This new species is only found in Daweishan area in Southeast Yunnan, China.